A Pd / ZnO-ZrO2 catalyst for hydrogen production by methanol steam reforming and its preparation method and application
By developing low precious metal-supported Pd/ZnO-ZrO2 catalysts, the problems of low H2 yield and low CO2 selectivity of existing catalysts are solved, and high catalytic activity and low cost effects are achieved.
Patent Information
- Application Number
- CN202310299567.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-24
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-03-24
AI Technical Summary
The existing catalysts have low H2 yield, low CO2 selectivity in methanol steam reforming, and high cost of precious metal catalysts.
A low-precious metal-supported Pd/ZnO-ZrO2 catalyst was developed, and a composite of ZnO and ZrO2 was synthesized by co-precipitation method, and a precursor suspension was immersed by wet method to synthesize a catalyst with high catalytic activity.
High catalytic activity and high CO2 selectivity are achieved, while reducing the cost of Pd, and the catalyst shows good stability in high temperature environments.
Smart Images

Figure CN116251589B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of methanol hydrogen production, and relates to a Pd / ZnO-ZrO2 catalyst for methanol steam reforming hydrogen production, and a preparation method and application thereof. Background Art
[0002] In recent years, economic and population growth have led to a sharp increase in energy demand, coupled with reduced oil reserves and environmental pollution, making it necessary to find alternative energy sources. The use of fossil fuels has a negative impact on the environment and human health. At the same time, its resources are non-renewable and continued mining may lead to depletion. Therefore, the development of renewable energy has become the biggest challenge at present. Hydrogen energy has become the most promising secondary energy source in the 21st century due to its high energy density and clean and pollution-free characteristics. Its source is almost inexhaustible and can be used to provide hydrogen power to other fuel cells such as proton exchange membrane fuel cells (PEMFC) and solid oxide fuel cells (SOFC), so people's interest in hydrogen has increased. However, the storage and transportation of hydrogen is the main obstacle to the widespread application of fuel cells because hydrogen has a low density and is flammable and explosive.
[0003] Catalytic reforming of liquid fuels into hydrogen is one of the promising ways to solve the challenge. Methanol is considered to be the most ideal hydrogen carrier due to its low cost, high hydrogen-to-carbon ratio, easy transportation, overcapacity, and wide application. Regarding methanol reforming technology, there are currently four ways to produce hydrogen: methanol steam reforming, methanol partial oxidation, methanol autoheating, and methanol decomposition to produce hydrogen. The latter three hydrogen production methods have the disadvantages of requiring oxygen to be introduced and low hydrogen production, poor reaction control that makes the catalyst easy to sinter, and high CO content. In contrast, methanol steam reforming to produce hydrogen does not require oxygen to be introduced, has high hydrogen production, and can react at a relatively low temperature (250-400°C), so it is widely used.
[0004] The performance of methanol steam reforming depends largely on the catalyst. Commercial Cu / ZnO / Al2O3 catalyst is the most commonly used catalyst in methanol steam reforming because it has high reactivity and selectivity at low reaction temperatures (200-350℃). However, its own thermal instability and combustion characteristics cause the active sites to easily agglomerate and deactivate in a high-temperature steam environment. After a period of high-temperature reaction, the stability drops sharply. Due to the agglomeration and deactivation of Cu, more and more by-products such as CO and CH4 are produced during the reaction, which is not conducive to the reaction. Palladium-based catalysts are considered to be a very promising copper substitute due to their own stability. At present, the research object of Pd-based catalysts in methanol steam reforming is mainly PdZn bimetallic system. On the one hand, due to the small specific surface area of ZnO, palladium atoms cannot be well dispersed, resulting in the agglomeration of Pd particles, the utilization rate of Pd atoms decreases, and the local agglomeration forms Pd clusters, which is not conducive to the reaction; on the other hand, in the PdZn bimetallic system, the palladium loading content usually needs to reach more than 3% to improve the SRM reaction activity and CO2 selectivity, which is not conducive to large-scale use and the cost is too high. Therefore, the PdZn system needs to be further improved and optimized to ensure high activity, high selectivity and high stability while improving the utilization rate of Pd atoms and reducing the cost of Pd use. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of low H2 yield, low CO2 selectivity and cost of precious metal catalysts in existing catalysts, develop a Pd / ZnO-ZrO2 catalyst with low precious metal loading and high catalytic activity, provide a preparation method of the catalyst and its application in methanol steam reforming, and compare the performance of Pd / ZnO-ZrO2 catalysts with different Pd contents in methanol steam reforming.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A Pd / ZnO-ZrO2 catalyst for hydrogen production by methanol steam reforming, characterized in that low-loaded Pd is used as an active component, a composite of ZnO and ZrO2 is used as a carrier, the molar ratio of Zn to Zr is 1.0-5.0, and the Pd content is 0.05-0.5%.
[0008] The preparation method of the above-mentioned Pd / ZnO-ZrO2 catalyst for hydrogen production by methanol steam reforming comprises the following steps:
[0009] Step 1. Weigh Zr(NO3)4·5H2O and dissolve it in deionized water, weigh Zn(NO3)2·6H2O and dissolve it in deionized water, then add the Zr(NO3)4·5H2O and Zn(NO3)2·6H2O solutions to the (NH4)2·CO3 precipitant solution, stir the mixed solution at 60-80°C for 2-3 hours, let it stand, centrifuge, and wash with water to obtain a solid powder, freeze, vacuum dry, grind, and calcine in a tubular furnace in an air atmosphere at a temperature of 400-600°C for 2-3 hours, and cool naturally to obtain a composite of ZnO and ZrO2.
[0010] Step 2. Add the ZnO and ZrO2 complex obtained in step 1 and ethylene glycol solvent into a flask, place it in a water bath for heating, add circulating cooling water for protection, and when the mixed solution reaches 80-100° C., add sodium tetrachloropalladate solution for stirring for 2-3 hours, then add ethanol for stirring, obtain solid powder after centrifugation, ethanol washing and water washing, and then freeze, vacuum dry and grind it, and then calcine it in a tubular furnace. The calcination atmosphere is a hydrogen-argon mixed gas containing 5-10% hydrogen by volume, the reduction temperature is 300-500° C., the reduction time is 2-3 hours, and the Pd / ZnO-ZrO2 catalyst is obtained after natural cooling.
[0011] In a preferred embodiment of the present invention, in step 1, the amount of (NH4)2·CO3 added is 4.0-4.5 g, which is dissolved in 30-40 mL of deionized water; the amount of Zr(NO3)4·5H2O added is 1.5-2.0 g, which is dissolved in 70-80 mL of deionized water; the amount of Zn(NO3)2·6H2O added is 5.5-6.0 g, which is dissolved in 20-30 mL of deionized water, allowed to stand for 20-40 min, washed with water 1-2 times, frozen for 2-3 h, and vacuum dried for 12 h.
[0012] In a preferred embodiment of the present invention, in step 2, 0.5-1.0 g of the composite of ZnO and ZrO2 is taken, the amount of ethylene glycol used is 50-150 mL, the concentration of the sodium tetrachloropalladate precursor solution used is 5-10 mg / mL, the amount of sodium tetrachloropalladate used is 0.138 mL-1.384 mL, the amount of ethanol added is 50-100 mL, ethanol washing is 1-2 times, water washing is 1-2 times, freezing time is 2-3 hours, and vacuum drying time is 10-12 hours.
[0013] Another technical solution of the present invention is:
[0014] The application of the above-mentioned Pd / ZnO-ZrO2 catalyst for producing hydrogen by methanol steam reforming in the methanol steam reforming reaction.
[0015] In a preferred embodiment of the present invention, the methanol steam reforming reaction is carried out in a fixed bed reactor, raw materials and the methanol steam reforming hydrogen production catalyst are added, and the vaporized reaction gas is blown with a carrier gas, the carrier gas is argon, the argon pressure is 0.1-0.5 MPa, and the argon flow rate is 10-20 mL / min. Programmed temperature activation is carried out, and after reaching the required temperature, the reaction is carried out at a constant temperature, the vaporization temperature is 100-150°C, the reaction temperature is 350-500°C, the reaction time is 4-6h, and the catalytic activity of the catalyst is detected.
[0016] In a preferred embodiment of the present invention, the raw materials are water and methanol, the water-to-methanol molar ratio is 1.0-1.5, the flow rate of the methanol-water mixed solution is 0.03-0.07 mL / min, and the volume space velocity is 10000-15000 h -1 The catalyst dosage is 50 to 150 mg.
[0017] The present invention has the following advantages:
[0018] 1. This method uses a composite of ZnO and ZrO2 synthesized by a co-precipitation method as a carrier, which has a large specific surface area, and then wet-impregnates the Pd synthesis precursor suspension, and obtains the Pd / ZnO-ZrO2 catalyst through the steps of washing, drying, calcining, etc.
[0019] 2. This method adopts wet preparation during the synthesis process, the reaction conditions are milder, the complexity is lower, and it is easier to achieve large-scale industrial production.
[0020] 3. The material synthesized by this method is resistant to high temperatures. As the temperature increases, the activity maintains an increasing trend. At higher reaction temperatures, the by-products CO and CH4 are less, and the CO2 selectivity remains high.
[0021] 4. The Zr element doped in the carrier synthesized by this method has the function of stabilizing the structure. When the molar ratio of Zn to Zr reaches an appropriate value, high activity, selectivity and stability can be maintained during the reaction.
[0022] 5.0.1Pd / ZnO-ZrO2 (Pd content: 0.1%) showed the best activity. After 5h of reaction, the methanol conversion rate reached 93.3% and the hydrogen production was as high as 1146.8 mol·g Pd -1 ·h -1 , CO2 selectivity reached 95.7%, CH4 was almost zero, and maintained good stability within 5 hours, with almost no decrease in hydrogen production activity. In addition, the catalyst has a precious metal content of only 0.1%, and Pd exists in a single atom form, which is 30 times lower than conventional Pd-based catalysts (Pd ≥ 3%), which greatly reduces the cost and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD patterns of Pd / ZnO-ZrO2 catalyst (six different amounts of sodium tetrachloropalladate)
[0024] Figure 2 Spherical aberration electron microscopy image of 0.1Pd / ZnO-ZrO2 (Pd content: 0.1%) catalyst
[0025] Figure 3 Diagram of the methanol steam reforming evaluation device for Pd / ZnO-ZrO2 catalyst, 1-injection pump, 2-Ar gas cylinder, 3-pressure reducing valve, 4-mass flow meter, 5-heating belt, 6-evaporator, 7-temperature controller, 8-reactor, 9-cold trap, 10-dryer, 11-gas chromatograph, 12-display screen, 13-soap film flow meter, 14-hydrogen generator, 15-air generator
[0026] Figure 4 The change of hydrogen yield per unit palladium in methanol steam reforming hydrogen production using Pd / ZnO-ZrO2 catalyst (six different sodium tetrachloropalladate dosages)
[0027] Figure 5 The change of methanol conversion rate in methanol steam reforming hydrogen production over Pd / ZnO-ZrO2 catalyst (six different sodium tetrachloropalladate dosages)
[0028] Figure 6 Figure 2. Changes in CO2 selectivity of Pd / ZnO-ZrO2 catalyst (six different sodium tetrachloropalladate dosages) in methanol steam reforming hydrogen production.
[0029] Figure 7 The stability diagram of hydrogen production of 0.1Pd / ZnO-ZrO2 (Pd content: 0.1%) catalyst in methanol steam reforming hydrogen production reaction DETAILED DESCRIPTION
[0030] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0031] Example 1
[0032] Weigh 4.04g (NH4) 2·CO3, 1.72g Zr (NO3) 4·5H2O and 5.95g Zn (NO3) 2·6H2O, the molar ratio of Zn to Zr is 5:1, dissolve them in 40mL, 80mL and 30mL deionized water respectively and stir, wait until the Zr (NO3) 4·5H2O and Zn (NO3) 2·6H2O solutions are clear and transparent, pour the Zr (NO3) 4·5H2O and Zn (NO3) 2·6H2O solutions into the (NH4) 2·CO3 solution, keep the temperature at 70℃ for 3h. Then let it stand for 30min, centrifuge it, wash it with water twice, freeze-dry the precipitate overnight, calcine it in a tube furnace, the calcination atmosphere is air, the calcination temperature is 500℃, the calcination time is 2h, grind it to obtain the composite of ZnO and ZrO2. Take 0.5g of the complex of ZnO and ZrO2, add 100mL of ethylene glycol solvent, heat to 100℃, then add 0.138mL of 10mg / mL Na2PdCl4 solution, and perform hydrothermal reaction for 3h. Then transfer the solution to a beaker, add 100mL of ethanol and stir for 30min, then centrifuge, wash twice with ethanol, and wash once with water. The obtained precipitate is freeze-dried with a freeze dryer and ground into solid powder P. The solid powder P is calcined in a tube furnace, the calcination atmosphere is a hydrogen-argon mixed gas containing 5% hydrogen by volume, the calcination temperature is 400℃, the calcination time is 2h, and after the calcination is completed and cooled naturally, grind and sieve to obtain the catalyst 0.1Pd / ZnO-ZrO2, named A. The Pd content in A is 0.1%.
[0033] The above material A was subjected to XRD phase analysis, such as Figure 1 As shown in the figure, the prepared sample particles are extremely small, showing only the signals of ZnO and ZrO2. Spherical aberration electron microscopy analysis of material A is performed, as shown in the figure. Figure 2 As shown, Pd in the prepared sample exists in the form of a single atom. The synthesized catalyst is granulated into 40-60 mesh, 100 mg of the catalyst is taken and placed in a sample tube, the ratio of quartz sand to sample is 1:3, and the sample tube is fixed in the reactor, as shown in FIG. Figure 3 The test conditions are as follows: the water-alcohol molar ratio is 1.2, the flow rate of the methanol-water mixed solution is 0.05 mL / min, the carrier gas is argon, the argon pressure is 0.3 MPa, the argon flow rate is 15 mL / min, and the volume space velocity is 12000 h -1 , the vaporization temperature is 120℃, the reaction temperature is 400℃, and the reaction time is 5h. Figure 4 As shown in Figure 2, the hydrogen yield of the catalyst is 108.5 mol·g Pd -1 ·h -1 .like Figure 5 As shown in FIG. 1 , the methanol conversion rate of the catalyst is 25.9%, which is less than 30%. Figure 6 As shown, the CO2 selectivity of the catalyst is 95.5%, which is greater than 95%.
[0034] Example 2
[0035] The preparation of the composite of ZnO and ZrO2 is the same as in Example 1, and the molar ratio of Zn to Zr is 5:1. Take 0.5g of the composite of ZnO and ZrO2, add 100mL of ethylene glycol solvent, heat to 100°C, then add 0.138mL of 10mg / mL Na2PdCl4 solution, and perform hydrothermal reaction for 3h. Then transfer the solution to a beaker, add 100mL of ethanol and stir for 30min, then centrifuge, wash with ethanol twice, and then wash with water once. The obtained precipitate is freeze-dried with a freeze dryer and ground into solid powder P. The solid powder P is calcined in a tubular furnace, the calcination atmosphere is a hydrogen-argon mixed gas containing 5% hydrogen by volume, the calcination temperature is 400°C, the calcination time is 2h, and after the calcination is completed, the catalyst 0.1Pd / ZnO-ZrO2 is obtained by grinding and sieving after natural cooling, and is named B. The content of Pd in B is 0.1%.
[0036] The above material B was subjected to XRD phase analysis, such as Figure 1 As shown in the figure, the prepared sample particles are extremely small, showing only the signals of ZnO and ZrO2. Spherical aberration electron microscopy analysis of material B is performed, as shown in the figure. Figure 2 As shown, Pd in the prepared sample exists in the form of single atoms. The synthesized catalyst was granulated into 40-60 mesh, 100 mg of the catalyst was placed in a sample tube, the ratio of quartz sand to sample was 1:3, and the sample tube was fixed in the reactor, as shown in FIG. Figure 3 The test conditions are as follows: the water-alcohol molar ratio is 1.2, the flow rate of the methanol-water mixed solution is 0.05 mL / min, the carrier gas is argon, the argon pressure is 0.3 MPa, the argon flow rate is 15 mL / min, and the volume space velocity is 12000 h -1 , vaporization temperature is 120℃, reaction temperature is 450℃, reaction time is 5h. Figure 4 As shown in Figure 2, the hydrogen yield of the catalyst is 1146.8 mol·g Pd -1 ·h -1 .like Figure 5 As shown in Figure 2, the methanol conversion rate of the catalyst is 93.3%. Figure 6 As shown in FIG. 1 , the CO2 selectivity of the catalyst is 95.7%, which is greater than 95%. Figure 7 As shown in the figure, the catalyst maintained good hydrogen production stability within 5 h of reaction.
[0037] Example 3
[0038] The preparation of the composite of ZnO and ZrO2 is the same as in Example 1, and the molar ratio of Zn to Zr is 5:1. Take 0.5g of the composite of ZnO and ZrO2, add 100mL of ethylene glycol solvent, heat to 100°C, then add 0.346mL of 10mg / mL Na2PdCl4 solution, and perform hydrothermal reaction for 3h. Then transfer the solution to a beaker, add 100mL of ethanol and stir for 30min, then centrifuge, wash with ethanol twice, and then wash with water once. The obtained precipitate is freeze-dried with a freeze dryer and ground into solid powder P. The solid powder P is calcined in a tubular furnace, the calcination atmosphere is a hydrogen-argon mixed gas containing 5% hydrogen by volume, the calcination temperature is 400°C, the calcination time is 2h, and after the calcination is completed and cooled naturally, the catalyst 0.25Pd / ZnO-ZrO2 is obtained by grinding and sieving, named C. The content of Pd in C is 0.25%.
[0039] The above C material was subjected to XRD phase analysis, such as Figure 1 As shown in the figure, the prepared sample particles are small and only show the signals of ZnO and ZrO2. The synthesized catalyst is granulated into 40-60 mesh, 100 mg of catalyst is taken and placed in a sample tube, the ratio of quartz sand to sample is 1:3, and the sample tube is fixed in the reactor, as shown in the figure. Figure 3 The test conditions are as follows: the water-alcohol molar ratio is 1.2, the flow rate of the methanol-water mixed solution is 0.05 mL / min, the carrier gas is argon, the argon pressure is 0.3 MPa, the argon flow rate is 15 mL / min, and the volume space velocity is 12000 h -1 , the vaporization temperature is 120℃, the reaction temperature is 400℃, and the reaction time is 5h. Figure 4 As shown in Figure 2, the hydrogen yield of the catalyst is 239.4 mol·g Pd -1 ·h -1 .like Figure 5 As shown in Figure 2, the methanol conversion rate of the catalyst is 61.2%. Figure 6 As shown, the CO2 selectivity of the catalyst is 96.5%, which is greater than 95%.
[0040] Example 4
[0041] The preparation of the composite of ZnO and ZrO2 is the same as in Example 1, and the molar ratio of Zn to Zr is 5:1. Take 0.5g of the composite of ZnO and ZrO2, add 100mL of ethylene glycol solvent, heat to 100°C, then add 0.346mL of 10mg / mL Na2PdCl4 solution, and perform hydrothermal reaction for 3h. Then transfer the solution to a beaker, add 100mL of ethanol and stir for 30min, then centrifuge, wash with ethanol twice, and then wash with water once. The obtained precipitate is freeze-dried with a freeze dryer and ground into solid powder P. The solid powder P is calcined in a tubular furnace, the calcination atmosphere is a hydrogen-argon mixed gas containing 5% hydrogen by volume, the calcination temperature is 450°C, the calcination time is 2h, and after the calcination is completed and cooled naturally, the catalyst 0.25Pd / ZnO-ZrO2 is obtained by grinding and sieving, named D. The Pd content in D is 0.25%.
[0042] The above D material was subjected to XRD phase analysis, such as Figure 1 As shown in the figure, the prepared sample particles are small and only show the signals of ZnO and ZrO2. The synthesized catalyst is granulated into 40-60 mesh, 100 mg of catalyst is taken and placed in a sample tube, the ratio of quartz sand to sample is 1:3, and the sample tube is fixed in the reactor, as shown in the figure. Figure 3 The test conditions are as follows: the water-alcohol molar ratio is 1.2, the flow rate of the methanol-water mixed solution is 0.05 mL / min, the carrier gas is argon, the argon pressure is 0.3 MPa, the argon flow rate is 15 mL / min, and the volume space velocity is 12000 h -1 , the vaporization temperature is 120℃, the reaction temperature is 400℃, and the reaction time is 5h. Figure 4 As shown in Figure 2, the hydrogen yield of the catalyst is 442.1 mol·g Pd -1 ·h -1 .like Figure 5 As shown in Figure 2, the methanol conversion rate of the catalyst is 91.5%. Figure 6 As shown, the CO2 selectivity of the catalyst is 95.2%, which is greater than 95%.
[0043] Example 5
[0044] The preparation of the composite of ZnO and ZrO2 is the same as in Example 1, and the molar ratio of Zn to Zr is 5:1. Take 0.5g of the composite of ZnO and ZrO2, add 100mL of ethylene glycol solvent, heat to 100°C, then add 0.692mL of 10mg / mL Na2PdCl4 solution, and perform hydrothermal reaction for 3h. Then transfer the solution to a beaker, add 100mL of ethanol and stir for 30min, then centrifuge, wash with ethanol twice, and then wash with water once. The obtained precipitate is freeze-dried with a freeze dryer and ground into solid powder P. The solid powder P is calcined in a tubular furnace, the calcination atmosphere is a hydrogen-argon mixed gas containing 5% hydrogen by volume, the calcination temperature is 400°C, the calcination time is 2h, and after the calcination is completed and cooled naturally, the catalyst 0.5Pd / ZnO-ZrO2 is obtained by grinding and sieving, named E. The Pd content in E is 0.5%.
[0045] The above E material was subjected to XRD phase analysis, such as Figure 1 As shown, the prepared sample has a weak PdZn alloy signal. The synthesized catalyst was granulated into 40-60 mesh, 100 mg of the catalyst was placed in a sample tube, the ratio of quartz sand to sample was 1:3, and the sample tube was fixed in the reactor, as shown in FIG. Figure 3 The test conditions are as follows: the water-alcohol molar ratio is 1.2, the flow rate of the methanol-water mixed solution is 0.05 mL / min, the carrier gas is argon, the argon pressure is 0.3 MPa, the argon flow rate is 15 mL / min, and the volume space velocity is 12000 h -1 , vaporization temperature is 120℃, reaction temperature is 400℃, and reaction time is 5h. After 5h reaction, if Figure 4 As shown in Figure 2, the hydrogen yield of the catalyst is 144.2 mol·g Pd -1 ·h -1 .like Figure 5 As shown in Figure 2, the methanol conversion rate of the catalyst is 68.9%. Figure 6 As shown, the CO2 selectivity of the catalyst is 96.1%, which is greater than 95%.
[0046] Example 6
[0047] The preparation of the composite of ZnO and ZrO2 is the same as in Example 1, and the molar ratio of Zn to Zr is 5:1. Take 0.5g of the composite of ZnO and ZrO2, add 100mL of ethylene glycol solvent, heat to 100°C, then add 1.384mL of 10mg / mL Na2PdCl4 solution, and perform hydrothermal reaction for 3h. Then transfer the solution to a beaker, add 100mL of ethanol and stir for 30min, then centrifuge, wash with ethanol twice, and then wash with water once. The obtained precipitate is freeze-dried with a freeze dryer and ground into solid powder P. The solid powder P is calcined in a tubular furnace, the calcination atmosphere is a hydrogen-argon mixed gas containing 5% hydrogen by volume, the calcination temperature is 400°C, the calcination time is 2h, and after the calcination is completed and cooled naturally, the catalyst 1Pd / ZnO-ZrO2 is obtained by grinding and sieving, named F. The content of Pd in F is 1.0%.
[0048] The above F material was subjected to XRD phase analysis, such as Figure 1 As shown in the figure, the prepared sample showed a relatively obvious signal of PdZn alloy. The synthesized catalyst was granulated into 40-60 mesh, 100 mg of catalyst was taken and placed in a sample tube, the ratio of quartz sand to sample was 1:3, and the sample tube was fixed in the reactor, as shown in the figure. Figure 3 The test conditions are as follows: the water-alcohol molar ratio is 1.2, the flow rate of the methanol-water mixed solution is 0.05 mL / min, the carrier gas is argon, the argon pressure is 0.3 MPa, the argon flow rate is 15 mL / min, and the volume space velocity is 12000 h -1 , the vaporization temperature is 120℃, the reaction temperature is 400℃, and the reaction time is 5h. Figure 4 As shown in Figure 2, the hydrogen yield of the catalyst is 170.6 mol·g Pd -1 ·h -1 .like Figure 5 As shown in FIG. 1 , the methanol conversion rate of the catalyst is 100.0%. Figure 6 As shown, the CO2 selectivity of the catalyst is 94.8%, which is less than 95%.
[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A Pd / ZnO-ZrO2 catalyst for hydrogen production by methanol steam reforming, characterized in that: Low-load Pd was used as the active component, a composite of ZnO and ZrO2 was used as the carrier, the molar ratio of Zn to Zr was 5.0, and the Pd content was 0.1%; The preparation method comprises the following steps: Step 1. Weigh Zr(NO3)4·5H2O and dissolve it in deionized water, weigh Zn(NO3)2·6H2O and dissolve it in deionized water, then add Zr(NO3)4·5H2O and Zn(NO3)2·6H2O solutions to (NH4)2CO3 precipitant solution, stir the mixed solution at 60~80℃ for 2~3 h, then centrifuge and wash with water to obtain solid powder, freeze, vacuum dry and grind, and then calcine in a tube furnace. The calcination atmosphere is air, the calcination temperature is 400~600℃, the calcination time is 2~3 h, and after natural cooling, a composite of ZnO and ZrO2 is obtained; wherein the amount of (NH4)2CO3 added is 4.0~4.5 g, which is dissolved in 30~40 mL deionized water; the amount of Zr(NO3)4·5H2O added is 1.72 g, which is dissolved in 70~80 mL deionized water to dissolve; Zn(NO3)2·6H2O was added in an amount of 5.95 g and dissolved in 20~30 mL deionized water; Step 2. Add the ZnO and ZrO2 complex obtained in step 1 and ethylene glycol solvent into a flask, place it in a water bath for heating, add circulating cooling water for protection, and when the mixed solution reaches 80~100℃, add sodium tetrachloropalladate solution for stirring, and the stirring time is 2~3 h; wherein 0.5 g of the ZnO and ZrO2 complex is taken, the concentration of the sodium tetrachloropalladate precursor solution used is 10 mg / mL, and the amount of sodium tetrachloropalladate used is 0.138 mL; add ethanol for stirring, and obtain a solid powder after centrifugation, ethanol washing and water washing, and then freeze, vacuum dry and grind it, and then calcine it in a tubular furnace. The calcination atmosphere is a hydrogen-argon mixture containing 5~10% hydrogen by volume. The reduction temperature is 300~500℃, and the reduction time is 2~3 h. After natural cooling, the Pd / ZnO-ZrO2 catalyst is obtained.
2. The Pd / ZnO-ZrO2 catalyst for producing hydrogen from methanol steam reforming according to claim 1, characterized in that: In step 1, let it stand for 20 to 40 minutes, wash with water 1 to 2 times, freeze for 2 to 3 hours, and vacuum dry for 12 hours.
3. The Pd / ZnO-ZrO2 catalyst for producing hydrogen from methanol steam reforming according to claim 1, characterized in that: In step 2, the amount of ethanol added is 50-100 mL, the ethanol is washed 1-2 times, the water is washed 1-2 times, the freezing time is 2-3 h, and the vacuum drying time is 10-12 h.
4. Use of the Pd / ZnO-ZrO2 catalyst for producing hydrogen by steam reforming of methanol according to claim 1 in a methanol steam reforming reaction.
5. The use of a Pd / ZnO-ZrO2 catalyst for producing hydrogen by steam reforming of methanol according to claim 4 in a methanol steam reforming reaction, characterized in that: The methanol steam reforming reaction is carried out in a fixed bed reactor, and raw materials and the methanol steam reforming hydrogen production catalyst are added, the raw materials are water and methanol, the water-to-methanol molar ratio is 1.0-1.5, the vaporized reaction gas is blown with a carrier gas, the carrier gas is argon, the argon pressure is 0.1-0.5 MPa, the argon flow rate is 10-20 mL / min, programmed temperature activation is carried out, and the reaction is carried out at a constant temperature after reaching the required temperature, the vaporization temperature is 100-150°C, the reaction temperature is 350-500°C, the reaction time is 4-6 h, and the catalytic activity of the catalyst is detected.
6. The use of a Pd / ZnO-ZrO2 catalyst for producing hydrogen by steam reforming of methanol according to claim 5 in a methanol steam reforming reaction, characterized in that: The flow rate of methanol-water mixed solution is 0.03-0.07 mL / min, and the volume space velocity is 10000-15000 h -1 , the catalyst dosage is 50~150 mg.
Citation Information
Patent Citations
Preparation method of Pd / ZnO catalyst for hydrogen production by methanol steam reforming
CN115414931A